Respon Siswa terhadap Media Pembelajaran Berbasis Game Edukasi Pada Materi SPLDV Kelas VIII SMP - Sahid, Nurdin Wahyu; Prihaswati, Martyana; Mawarsari, Venissa Dian (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
Educational games have become a popular learning medium among students. "The Journey of Sempoamen" is an educational game-based mathematics learning medium on the topic of systems of linear equations in two variables (SPLDV). The purpose of this study is to obtain student responses to determine the practicality level of the developed medium. This type of research is descriptive qualitative research. The data collection techniques in this study used interviews and student response questionnaires. The subjects of this study were eighth-grade junior high school students in Klaten Regency, Indonesia. The results of this study indicate that the developed medium has met the criteria for being highly practical, with an overall average score of 3.80. The display aspect received an average score of 3.78, categorized as highly practical. For the material aspect, the medium received an average score of 3.79, also categorized as highly practical. In terms of language, the developed medium received an average score of 3.80, indicating it is highly practical. The ease of use aspect received an average score of 3.85, categorized as highly practical. Based on these results, it can be concluded that the development of the educational game medium "The Journey of Sempoamen" is highly practical and ready to be used in the learning process.